Corncob Modified By Cufe Layered For Oxytetracycline Removal From Aqueous Solution - Chandran, Dhiwakar (Universiti Sains Malaysia, 2022)
In this study, corncob-based activated carbon(CCAC) was prepared from waste biomass to study the removal of OTC in an aqueous solution. The experimental design discovered that the CCAC is mainly influenced by Cu-Fe impregnation ratio, radiation power and time. The optimal condition of CCAC preparation with radiation power of 364 W, and radiation time of 20 min, resulted in OTC removal and CCAC’s yield of 13.6431 mg/g and 20.85%. The characterization of CCAC is determined mesoporous in nature, high surface area and heterogeneous types of pore structures. The surface functionality of CCAC is available multiple functional groups function as active sites for OTC chemical and physical binding. For the batch studies, the effect of initial concentration, the amount of OTC removed by the optimized condition of CCAC, increases over time. The study of the effect of temperature has an increasing removal effect. Equilibrium pH of 8 yields the highest removal percentage in the effect of the solution pH study. Isotherm model analysis resulted in Freundlich as the best-suited model for the maximum monolayer capacity. The kinetic study revealed that the adsorption of OTC onto CCAC follows a pseudo-second-order kinetic model with minimal k2 value. The thermodynamics of OTC-CCAC adsorption proves the endothermic nature as follows the effect of temperature study..